2021
DOI: 10.18196/ijnp.v5i1.11186
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship among Parenting Style, Self-Regulation, and Smartphone Addiction Proneness in Indonesian Junior High School Students

Abstract: Background: Smartphone addiction leads to physical, psychological, and social consequences for users, particularly for adolescent users, as psychological development is still in the process of maturation. Individual and family characteristics are shown to contribute to shaping adolescent’s behavior related to smartphone usage. Specifically, perceived parenting style and self-regulation have been reported as significant factors influencing smartphone addiction among adolescents.Objective: This study aims to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…This rate notably diverges from those observed in other Asian contexts. For context, addiction rates in India fluctuate between 39% and 67% [2,53], while only 21.3% of Chinese undergraduates [54], 11.4% of Indonesian junior high students [55], 35.2% of South Korean adolescents [56], and 62.6% of Filipino adolescents [57] are reported as addicted. Interestingly, even within Thailand, there is a stark contrast in SA rates, as evidenced by a recent study by Chinwong et al [37], which found a 49% addiction rate among undergraduates in Northern Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…This rate notably diverges from those observed in other Asian contexts. For context, addiction rates in India fluctuate between 39% and 67% [2,53], while only 21.3% of Chinese undergraduates [54], 11.4% of Indonesian junior high students [55], 35.2% of South Korean adolescents [56], and 62.6% of Filipino adolescents [57] are reported as addicted. Interestingly, even within Thailand, there is a stark contrast in SA rates, as evidenced by a recent study by Chinwong et al [37], which found a 49% addiction rate among undergraduates in Northern Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…This study underscores the pronounced prevalence of smartphone addiction (SA) among Thai Muslim students, with a staggering 70% showing signs of addiction, a rate that sharply contrasts with other Asian countries. For context, addiction rates in India fluctuate between 39% and 67% [2,53], while only 21.3% of Chinese undergraduates [54], 11.4% of Indonesian junior high students [55], 35.2% of South Korean adolescents [56], and 62.6% of Filipino adolescents [57] are reported as addicted. Interestingly, even within Thailand, there's a stark contrast in SA rates, as evidenced by a recent study by Chinwon et al [38], which found a 49% addiction rate among undergraduates in Northern Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…Kecanduan gadget di kalangan siswa tidak hanya mengganggu prestasi di sekolah, tetapi juga berkontribusi terhadap masalah fisik, emosional, dan kognitif mereka. Oleh karena itu, berbagai upaya telah dilakukan untuk mengurangi dan mengelola penggunaan gadget secara tepat, misalnya dengan meningkatkan kesadaran remaja akan bahaya penggunaan gadget secara berlebihan dan mengajarkan untuk pengelolaan waktu (Fatkuriyah & Sun-Mi, 2021;Surat et al, 2021).…”
Section: Gambar 3 Kegiatan Ice Breaking Yang Bertujuan Untuk Mengenal...unclassified